NEURO PROGENITOR CELLS (NPCS) AND PPARγ EXPRESSION IN THE BRAIN OF PROTEIN-DEFICIENT RATS AFTER ADMINISTRATION OF PASAK BUMI (Eurycoma longifolia Jack) EXTRACT - Didik Dwi Sanyoto; Triawanti Triawanti; Dimas Ikhsan Airlangga (Berkala Kedokteran, 2022)
Abstract: Malnutrition due to protein deficiency disrupts the neurogenesis process that affects cell development and brain function. One of the efforts to overcome the matter is to use the pasak Bumi (Eurycoma longifolia Jack) which has compounds believed to increase the process of neurogenesis. The aim of study to analyze the effect of pasak bumi extract on the expression of NPCs (Tuj-1) and PPARγ cell in the brains of malnourished rats. Groups of experimental animals that were were divided into 5 groups, namely (P1) malnourished rats + placebo (aquades); (P2) malnourished rats + pasak bumi extract (EPB) 7,5 mg/kg BW; (P3) malnourished rats + EPB 15 mg/kg BW; (P4) malnourished rats + EPB 22,5 mg/kg BW; (P5) malnourished rats + EPB 30 mg/kg BW. As a control, normal rats were used which were given a placebo. Parameters examined include Tuj-1 and PPARγ using immunohistochemistry procedure. The results showed that the P3 group (15 mg/kg BW) had more cells expressing Tuj-1 than the other doses. There was a significant difference between the KP and the P3, P4, and P5 groups. There was no significant difference in the expression of PPARγ in all malnourished groups with EPB and KN intervention. Conclusion: extract of pasak bumi was able to improve the neurogenesis process in malnutrition but not PPARγ. Keywords: Malnutrition, pasak bumi extract, NPCs, Tuj-1, PPARγ